P Penyuluhan dan Pelatihan Peranan Orang Tua dalam Mendidik Anak di Desa Kiram pada Masa Pandemi COVID-19: Counseling and Training on the Role of Parents in Educating Children in Kiram Village During the COVID-19 Pandemic - Jarkawi, Jarkawi; Yuliansyah, Muhammad; Anwar, Kasypul (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2024)
The COVID-19 pandemic has had an impact on all sectors of life, including the education sector. The learning process, which is usually conducted in classrooms, has been shifted to home-based learning to prevent and reduce the spread of the COVID-19 virus in educational settings. Most parents in Kiram Village work as fish farmers, and their operations often involve their children, especially during the fish harvesting season. As a result, during the COVID-19 pandemic, children sometimes did not participate in the learning process or study at home. Consequently, they fell behind in their studies, which negatively affected their academic performance. The lack of awareness about the importance of parents' roles in their children's learning process also negatively impacted children's academic achievements. One effort to provide knowledge and understanding about the role of parents in educating their children was through counseling and training sessions on parental involvement in children's education at home, especially during the COVID-19 pandemic. These sessions used a psycho-educational approach, employing methods such as lectures, Q&A sessions, discussions, skill training, and problem-solving. Media tools like problem cards and solution cards were utilized. he results of the counseling and training showed an increase in parents' knowledge and a change in their perceptions regarding their role in supporting their children's learning at home, particularly during the COVID-19 pandemic.